(untitled) (Jóvenes en la Ciencia, 2024)
chromium (Cr (VI)) from industrial leachates. The physicochemical characterization of the leachate was performed, along with the determination of the maximum Cr (VI) removal using adsorption isotherms. Additionally, an impregnation method with γ-Fe2O3 nanoparticles was applied. The hypothesis that impregnation would enhance Cr (VI) removal was confirmed, showing that impregnated biochar achieved significantly higher removal compared to non-impregnated biochar.